Female Circumcision: Is It Still Happened? Legal Or Illegal? - Lanny, Ramli (Opción, 2019)
Beside popular in Africa, female circumcision also known well in Indonesia. In certain areas such as include: Banten, Serang, Surabaya, Situbondo, and also on the island of Madura, female circumcision still happened until now. In patriarchy system that centered at male power in societies, male should be more dominant than female. The greater number of females are troublesome. It means, there are a lot of female population and in patriarchy system view the female should in lower position in society. Female no important get the good education, so that female in the society do not optimal know about the knowledge, know about the healthy. Because of that, the number of females that have no enough knowledge and have no enough understanding about healthy potential not support the develop society. Because of lack knowledge and lack understanding about healthy, the female obeys to do female circum- cision. Because the female as great number in population make the female circumcision still happened until now even though the female circumcision forbidden. It needs guidance and counseling for female who have not given birth to children and for female who have given birth to children so that they have an awareness that every human being has the same rights. Because of not proper knowledge and education for female in the certain area, female circumcision still happened although prohibition by Minister of Health Reg- ulation RI Number 6 Year 2014. This research aims is to avoid the female cir- cumcision from several society that affect women health. By using socio legal research, purposive random sampling and in depth interview as method, this research should have findings that men and women have equal rights in terms of sexuality and reproductive By using socio legal research, purposive random sampling and in depth interview as method, this research should have findings that men and women have equal rights in terms of sexuality and reproductive health because the aims from this research is reach the same right for male and female. Finally, after female aware about the same right, female understanding the access of healthy and the end the female circum- cision not happened in society.